How to connect the resistance wire and lead wire of the resistance temperature sensor element

By inserting spiral resistor lines into the ceramic insulator and connecting them with low-softening point glass powder, the miniaturization and impact resistance of the temperature measurement resistors in extreme environments such as rocket fuel tanks are solved, and the temperature measurement effect with high accuracy and rapid response is achieved.

JP7626357B2Active Publication Date: 2025-02-04YAMARI INDS
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023176249
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-10-11
Publication Date
2025-02-04
Estimated Expiration
2041-02-02

AI Technical Summary

Technical Problem

The prior art is difficult to miniaturize the temperature measurement resistor in extreme environments (such as rocket fuel tanks), while maintaining high measurement accuracy, rapid response and impact resistance, and there are limitations on hysteresis characteristics caused by thermal cycles.

Method used

A spiral resistive wire is used to insert into the insulating powder of the ceramic insulator, and a cured connection is formed by mixing the glass powder at low softening point and the resistive wire and the insulator to reduce the strain caused by thermal circulation, and the low-temperature connection method is used to avoid recrystallization of the resistive wire.

Benefits of technology

It realizes the miniaturization of the temperature measuring resistor body in extreme environments, maintains high measurement accuracy and rapid response, enhances impact resistance and heat cycling capabilities, and avoids breakage and unstable connection of resistor lines.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007626357000006
    Figure 0007626357000006
  • Figure 0007626357000007
    Figure 0007626357000007
  • Figure 0007626357000008
    Figure 0007626357000008
Patent Text Reader

Abstract

To provide a temperature measuring resistor element, which, even if miniaturized, can overcome the strict limitations of hysteresis characteristics as a temperature measuring resistor, can maintain the high measurement accuracy and response characteristics, has excellent durability, and, for example, is suitable for applications such as rocket and also to provide a method of manufacturing the temperature measuring resistor element.SOLUTION: An insulating powder 4 is composed of a mixed glass powder containing two kinds of amorphous glass powders of a first glass powder 40 and a second glass powder 41 having the softening point temperature lower than that of the first glass powder. The temperature measuring resistor element has a connection structure in which the first glass powders 40, the first glass powder 40 and a resistance wire 3, or the first glass powder 40 and the inner surface of an insulator hole 20 are connected via the second glass powder 41 which is softened or melted to be deformed and solidified.SELECTED DRAWING: Figure 6
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resistance temperature sensor element formed by inserting a coil of spiral resistance wire into the insulator hole of a ceramic insulator and fixing the resistance wire inside the insulator hole via insulating powder, and in particular to a resistance temperature sensor element that can be miniaturized and is suitable for use in harsh environments such as rocket fuel tanks, where there is great impact, vibration and large temperature changes, and a method for manufacturing such a resistance temperature sensor element. [Background technology]

[0002] For example, resistance temperature detectors (temperature sensors) mounted on rocket fuel tanks are required to be compact, have excellent shock and vibration resistance, and have a high level of responsiveness to instantly detect and respond to the rocket's instantly changing combustion state. The elements (resistance temperature detector elements) built into resistance temperature detectors for general industrial use are generally sized, for example, with an outer diameter of φ3.0 mm and a length of about 30 mm, but for the above-mentioned rockets, dimensions of an outer diameter of φ1.0 mm or less and a length of 10 mm or less are usually required, and the wire diameter of the resistance wire used inside is about 0.01 mm. In addition, since rockets are subjected to thermal cycles from room temperature to liquid hydrogen temperature or liquid oxygen temperature, the resistance temperature detector is subject to strict restrictions on its hysteresis characteristics in order to maintain high temperature measurement accuracy.

[0003] Generally, as a resistance temperature sensor element that can be used under conditions of large shocks and vibrations, a type in which a spiral resistance wire is fitted into a hole in an alumina insulator and the coil is filled with insulating powder mainly made of alumina or magnesia and fixed in place is widely used (see, for example, Patent Documents 1 and 2). As another structure, a spiral resistance wire is partially fixed with insulating glass powder or the like (partially fixed type) is also known (see, for example, Non-Patent Documents 1 and 2).

[0004] However, if a resistance thermometer element having such a conventional structure is miniaturized and used, for example, as a resistance thermometer for a rocket as described above, the generation of thermal stress due to thermal cycling is unavoidable, making it difficult to meet the strict restrictions on hysteresis characteristics, and there are limits to the improvement of measurement accuracy and responsiveness. In addition, the resistance wire also has a thin wire diameter as described above, which poses durability problems. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Publication No. 4-5527 [Patent Document 2] JP 2019-2874 A [Non-patent literature]

[0006] [Non-Patent Document 1] Thermal Developments International Ltd. "TDI Catalogue" ("Hand made platinum resistance temperature detectors"), February 2004, Internet, retrieved November 13, 2020, (URL: http: / / www.tdi.co.uk / pdfs / tdi-cat.pdf) (page 6) [Non-Patent Document 2] Thermal Developments International Ltd. "Information Sheet 3: Advantages of Wire Wound Detectors" ("TDI Information Sheet Why Wire Wound?"), December 2009, Internet, retrieved November 13, 2020, (URL: http: / / www.tdi.co.uk / pdfs / TDI-Information-Sheet-3.pdf) (page 3) Summary of the Invention [Problem to be solved by the invention]

[0007] Therefore, in consideration of the above-mentioned situation, the problem that the present invention aims to solve is to provide a resistance temperature sensor element that can clear the strict hysteresis characteristic restrictions as a resistance temperature sensor even when miniaturized, maintains high measurement accuracy and response characteristics, and has excellent durability, making it suitable for applications such as rockets, and a manufacturing method for such a resistance temperature sensor element. [Means for solving the problem]

[0008] In view of the current situation, the inventors conducted extensive research and discovered that in a device in which a typical spiral resistance wire coil is fitted into a hole in an alumina insulator and insulating powder is filled around the coil to secure it in place, by using a mixed glass powder containing two types of amorphous glass powder as the insulating powder and providing a connecting structure in which one of the glass powders is softened or melted and deformed / solidified during the manufacturing process, it is possible to reduce the generation of thermal stress due to thermal cycles, overcome the strict limitations of the hysteresis characteristics required for a resistance temperature sensor, and improve impact resistance and vibration resistance, thereby completing the present invention.

[0009] That is, the present invention includes the following inventions. (1) A resistance temperature sensor element in which a spiral coil of resistance wire is inserted into an insulator hole of a ceramic insulator and an insulating powder is filled into the gap between the insulator hole and the resistance wire, thereby fixing the resistance wire inside the insulator hole, wherein the insulating powder is made of a mixed glass powder containing two types of amorphous glass powder, namely a first glass powder and a second glass powder having a softening point temperature lower than that of the first glass powder, and the resistance wire is connected to the first glass powder, the first glass powder and the resistance wire, or the first glass powder and the inner surface of the insulator hole via the second glass powder that has been softened or melted and deformed and solidified.

[0010] (2) The temperature sensor element according to (1), wherein the average particle size, which is the particle size at 50% of the integrated value in the particle size distribution of the first glass powder obtained by a Coulter counter method, is larger than the average particle size, which is the particle size at 50% of the integrated value in the particle size distribution of the second glass powder obtained by a laser diffraction / scattering method. Hereinafter, the average particle size of the first glass powder referred to in this specification is the particle size at an integrated value of 50% in the particle size distribution determined by the Coulter counter method, and the average particle size of the second glass powder is the particle size at an integrated value of 50% in the particle size distribution determined by the laser diffraction / scattering method.

[0011] (3) The resistance temperature sensor element according to (2), wherein the first glass powder is spherical.

[0012] (4) A resistance temperature sensor element as described in (2) or (3), which satisfies the following formula (A1), when the inter-wire distance in the axial direction of the coil center axis of the spiral resistance wire inserted in the insulator is α (mm) and the average particle size of the first glass powder (particle size at 50% cumulative value in particle size distribution obtained by Coulter counter method) is β (mm).

[0013]

number

[0014] (5) A resistance temperature sensor element according to any one of (1) to (4), wherein the mixed glass powder contains 90 weight percent or more of the first glass powder, and the first glass powder has a thermal expansion coefficient closer to the thermal expansion coefficient of the resistance wire than the second glass powder.

[0015] The inventor also independently studied the mechanism by which platinum wire, which is commonly used as resistance wire for temperature measuring resistors, becomes more susceptible to breakage when its diameter approaches 0.01 mm, and obtained new findings. That is, when the wire diameter approaches 0.01 mm, platinum resistance wire easily recrystallizes when heated, and by simply heating at 700°C and 1010°C for one hour, the recrystallized structure is surpassed and the crystal grains become coarse, as shown in the photographs in Figure 11, and the coarsened crystal grains form a bamboo node-like structure (so-called bamboo structure) that crosses the wire diameter. As can be seen in the photograph (Figure 3) showing the actual breakage location in a test in a severe vibration field such as the combustion vibration of a rocket, when the resistance wire is partially fixed, the severe vibration applied to the resistance wire causes the wire to break at the boundary between the fixed part and the free part. This phenomenon is largely influenced by the bamboo node-like structure caused by the coarsening of the crystal grains of the resistance wire, so manufacturing and heat treatment conditions that do not cause such a structure are required. From a correlation test between the heat treatment temperature / time and the growth of crystal grains, it was found that the maximum temperature at which a platinum resistance wire can remain in a recrystallized structure after heating for about one hour is about 500°C. Therefore, the following inventions (6), (7), and (9) were devised.

[0016] (6) The resistance temperature sensor element according to any one of (1) to (5), wherein the resistance wire is a platinum resistance wire, the first glass powder is a glass powder having a softening temperature of 500°C or more, and the second glass powder is a glass powder having a softening temperature of less than 500°C, and the connection structure is a structure in which the first glass powders, the first glass powder and the resistance wire, or the first glass powder and the inner surface of the insulator hole are connected to each other via the second glass powder that has been deformed and solidified by softening or melting due to heating at less than 500°C.

[0017] (7) The resistance temperature sensor element according to (6), wherein the resistance wire and the lead wire are connected by a low-temperature solder material having a liquidus temperature of less than 500°C.

[0018] (8) A method for manufacturing a resistance temperature sensor element in which a spiral coil of resistance wire is inserted into an insulator hole of a ceramic insulator and an insulating powder is filled into the gap between the insulator hole and the resistance wire, thereby fixing the resistance wire inside the insulator hole, the insulating powder being a mixed glass powder containing two kinds of amorphous glass powders, i.e., a first glass powder and a second glass powder having a softening point temperature lower than that of the first glass powder, and the insulating powder is heated at a temperature lower than the softening point temperature of the first glass powder and higher than or equal to the softening point temperature of the second glass powder while the insulating powder is filled, to soften or melt the second glass powder, and then cooled and solidified, thereby forming a connection structure in which the first glass powders are connected to each other, the first glass powder and the resistance wire, or the first glass powder and the inner surface of the insulator hole are connected via the second glass powder that has been softened or melted, deformed, and solidified.

[0019] (9) A method for manufacturing a resistance temperature sensor element according to (8), wherein the resistance wire is a platinum resistance wire, the first glass powder is a glass powder having a softening temperature of 500°C or higher, the second glass powder is a glass powder having a softening temperature of less than 500°C, and the heat treatment is a heat treatment at a temperature less than 500°C and not less than the softening point temperature of the second glass powder.

[0020] (10) The method for producing a resistance temperature sensor element according to (8) or (9), wherein the resistance wire and the lead wire are connected by brazing.

[0021] (11) A method for manufacturing a resistance temperature sensor element as described in (10), in which the soldering connection is a process in which a solder layer provided on the connection end of the lead wire on the resistance wire side is brought into contact with or close to the connection end of the resistance wire, and a position of the lead wire away from the solder layer is heated to melt the solder layer by heat transfer caused by the heating and connect it to the resistance wire.

[0022] (12) The method for manufacturing a resistance temperature sensor element according to (11), wherein the lead wire is heated by a pulse laser welder using a predetermined number of pulse heating processes. Effect of the Invention

[0023] According to the above-described resistance temperature sensor element and manufacturing method of the resistance temperature sensor element of the present invention, the insulating powder is made of a mixed glass powder containing two types of glass powder, namely, a first glass powder and a second glass powder having a softening point temperature lower than that of the first glass powder, and the first glass powder, the first glass powder and the resistance wire, or the first glass powder and the inner surface of the insulator hole have a connection structure in which the first glass powders are connected to each other, the first glass powder and the resistance wire, or the first glass powder and the inner surface of the insulator hole are connected to each other via the second glass powder that has been softened or melted and deformed and solidified. Therefore, unlike conventional insulating powders made of alumina or magnesia, it is possible to use glass powder whose thermal expansion coefficient is close to that of the resistance wire by adjusting the thermal expansion coefficient, thereby minimizing the generation of thermal stress due to thermal cycles, and the resistance temperature sensor can be provided with good hysteresis characteristics that are resistant to temperature changes, while maintaining high measurement accuracy and response characteristics. Furthermore, since the resistance wire has a connecting structure using the second glass powder as described above, it is possible to prevent the resistance wire from moving internally and being damaged, and since the thermal expansion coefficient can be set as described above, it is possible to realize a structure that is less susceptible to stress due to differences in thermal expansion, thereby providing a product with excellent durability that can withstand impact and vibration.

[0024] Furthermore, when the average particle size of the first glass powder is larger than the average particle size of the second glass powder, the packing density of the mixed glass powder can be stably increased, providing a product with higher measurement accuracy and higher durability.

[0025] In addition, when the first glass powder is spherical, the mixed glass powder (insulating powder) added from one end of the insulator hole flows through the space inside the coil of the spiral resistance wire inserted inside, and then the first glass powder passes between the wires of the resistance wire to reach the outside (between the resistance wire and the inner wall of the insulator hole), and as a result, the spiral resistance wire can be firmly fixed inside the insulator by the glass powder.

[0026] Furthermore, when the inter-wire distance in the central axis direction of the spiral resistance wire coil inserted into the insulator is α (mm) and the average particle size of the first glass powder is β (mm), if the following formula (A1) is satisfied, the first glass powder can more reliably pass between the wires of the resistance wire to reach the outside (between the resistance wire and the inner wall of the insulator hole), the spiral resistance wire coil can be more reliably fixed inside the insulator by the glass powder, the vibrations applied to the resistance wire in a high-vibration field can be more reliably absorbed, and durability can be reliably increased.

[0027]

number

[0028] In addition, when the mixed glass powder contains 90 weight percent or more of the first glass powder, and the first glass powder has a thermal expansion coefficient closer to that of the resistance wire than the second glass powder, by making the thermal expansion coefficient of the first glass powder, which contains 90 weight percent or more, closer to that of the resistance wire, the generation of thermal stress due to thermal cycles is reduced, and when used as a resistance temperature sensor, resistance value fluctuations due to hysteresis are suppressed, the sensor is resistant to temperature changes, and high measurement accuracy and response characteristics can be maintained, while the material of the second glass powder, which has little effect on hysteresis, can be selected relatively freely.

[0029] Furthermore, when the resistance wire is a platinum resistance wire, the first glass powder is made of glass powder having a softening temperature of 500°C or higher, and the second glass powder is made of glass powder having a softening temperature of less than 500°C, and the connecting structure is a structure in which the first glass powders, the first glass powder and the resistance wire, or the first glass powder and the inner surface of the insulator hole are connected to each other via the second glass powder that has been softened or melted by heating at less than 500°C and deformed and solidified, even if the platinum resistance wire is made thin, it is possible to prevent the formation of a bamboo node-like structure, and to provide a small-sized resistance wire that has excellent durability and can withstand impact and vibration.

[0030] Furthermore, when the resistance wire and lead wire are soldered together, the resistance value remains stable even when measurements are repeatedly taken at extremely low temperatures, such as the temperature of liquid hydrogen, and at room temperature. In particular, in the low temperature range of room temperature to 20 K (-253°C), there is no resistance value fluctuation due to mutual reaction between the solder material and the resistance wire, achieving a stable connection, i.e., a stable resistance value.

[0031] In addition, when the resistance wire and lead wire are connected with a low-temperature solder having a liquidus temperature of less than 500°C, the above-mentioned deterioration of the platinum wire (the occurrence of bamboo-like knotty structure) can be prevented, and breakage in a severe vibrating field can be prevented.

[0032] Furthermore, if the brazing connection is a process in which a solder paste provided on the connection end of the lead wire on the resistance wire side is brought into contact with or close to the connection end of the resistance wire, a position of the lead wire away from the solder paste is heated, and the solder paste is melted by heat transfer from the heating to connect to the resistance wire, the melting of the solder material during connection can be completed in a short time, unnecessary heat input to the resistance wire is suppressed, and the occurrence of the bamboo knot-like structure can be prevented. Also, when connecting, the lead wire expands due to heat, so it stretches slightly and the soldering of the resistance wire and the solidification of the solder can be completed quickly.

[0033] Furthermore, when the lead wire is heated by a process using a pulse laser welder that applies pulse heating a predetermined number of times, the placed solder portion is not directly heated by irradiating it with a laser, so unnecessary heating of the resistance wire can be avoided by shifting the focus of the laser away from the resistance wire.Furthermore, by applying pulse heating for only the number of sets required to melt the placed solder that has been determined in advance, for example five pulses per set, the heat input to the excess solder material can be reduced as much as possible, the occurrence of the bamboo knot-like structure can be more reliably prevented, and quality can be stabilized and production efficiency can be improved. [Brief description of the drawings]

[0034] [Figure 1] SEM photograph of the crystal grains of a platinum resistance wire with a wire diameter of 0.0125 mm after heat treatment at 700°C for 1 hour. [Diagram 2]SEM photograph of the crystal grains of a platinum resistance wire with a wire diameter of 0.0125 mm after heat treatment at 1010℃ for 1 hour. [Diagram 3] 1 is an SEM photograph showing a broken portion of a sample of Comparative Example 1. [Figure 4] FIG. 1 is an explanatory diagram showing the configuration of a resistance temperature detector element according to a representative embodiment of the present invention. [Diagram 5] SEM photo of a cross section after insulating powder was filled into an insulator hole together with a resistance wire and then heat treated. [Figure 6] FIG. 4 is a schematic diagram showing the state inside an insulator hole filled with insulating powder. [Figure 7] SEM photo of a cross section after insulating powder was filled into an insulator hole together with a resistance wire and then heat treated. [Figure 8] FIG. 4 is an explanatory diagram showing a method for brazing a resistance wire and a lead wire. [Figure 9] 1 is a graph showing the distribution of temperature deviation changes before and after a thermal cycle test. [Figure 10] 1 is an X-ray photograph of a passing sample of Example 1 and a failing sample of Comparative Example 1. [Figure 11] 1 is a graph showing the distribution of temperature deviation changes before and after a vibration test. [Figure 12] 13 is an SEM photograph of the structure of the outer surface of the connection part of the connection sample of Example 3. [Figure 13] 13 is an SEM photograph of the structure of the outer surface of the connection part of the connection body sample of Example 2. [Figure 14] Stereomicroscope photo of the fractured area. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0035] Next, an embodiment of the present invention will be described in detail with reference to the accompanying drawings.

[0036] As shown in Fig. 4, the resistance temperature sensor element 1 according to the present invention is configured such that a coil (coil-shaped resistance wire coil) which is a spiral resistance wire 3 is inserted into an insulator hole 20 of a ceramic insulator 2, and insulating powder 4 is filled into the gap between the insulator hole 20 and the resistance wire 3, thereby fixing the resistance wire 3 inside the insulator hole 20. The resistance wire 3 can be any known resistance wire depending on the application, such as a platinum resistance wire. An extension lead wire 5 is connected to the base end side of the resistance wire 3. The lead wire 5 can be any known resistance wire depending on the application, such as a platinum-rhodium alloy, just like the resistance wire.

[0037] In the present invention, the insulating powder 4 is a mixed glass powder containing two kinds of glass powder, a first glass powder and a second glass powder having a lower softening point than the first glass powder, and the first glass powder, the first glass powder and a resistance wire, or the first glass powder and an inner surface of an insulator hole are connected to each other through the second glass powder that has been softened or melted and deformed and solidified. For example, FIG. 5 shows a cross-sectional photograph of an insulating powder containing 5% second glass powder (glass with a softening temperature of 394° C.) and the rest being first glass powder with a softening temperature of 700° C. or higher, filled into an insulator hole together with a resistance wire, heated for 10 minutes at a heat treatment temperature of 450° C. to melt only the second glass powder, and cooled to solidify. As can be seen from the photograph in FIG. 5, the molten second glass powder melts so as to connect the first glass powder with a high melting point.

[0038] Unlike conventional alumina or magnesia powders, the thermal expansion coefficient of glass powder can be easily adjusted. Therefore, by making the thermal expansion coefficient of glass powder close to that of the resistance wire 3, it is possible to obtain a resistance temperature sensor with good hysteresis characteristics that are resistant to temperature changes and reduce the generation of thermal stress due to thermal cycles.

[0039] The mixing ratio of the first glass powder to the second glass powder ((first glass powder) / (second glass powder)) (in this specification, "mixing ratio" refers to a ratio by mass) is preferably 85 / 15 to 95 / 5. In the case where the first glass powder is contained at 90 weight percent or more and the first glass powder has a thermal expansion coefficient closer to that of the resistance wire compared to the second glass powder, the thermal expansion coefficient of the first glass powder contained at 90 weight percent or more is made closer to that of the resistance wire, so that the resistance value fluctuation due to the above-mentioned hysteresis when used as a resistance temperature sensor can be more reliably suppressed. For example, the thermal expansion coefficient of the first glass powder is set to be equal to the thermal expansion coefficient of a platinum resistance wire (about 88×10 -7 / ℃).

[0040] The second glass powder may deteriorate the hysteresis characteristics due to the softening glass having a different expansion coefficient, but this effect can be suppressed by increasing the mixture ratio of the first glass powder (85 / 15 to 95 / 5) and decreasing the ratio of the second glass powder as described above. The material of the second glass powder, which has little effect on the hysteresis, can be selected relatively freely.

[0041] The first glass powder and the second glass powder are mixed evenly using a mixer or the like, and only the second glass powder, which has a low melting point and an expansion coefficient different from that of the resistance wire 3, softens or melts, and partially intervenes in a deformed and solidified state between the first glass powders (main material), between the first glass powder and the resistance wire 3, or between the first glass powder and the inner surface of the insulator hole 20, forming the above-mentioned connection structure. This results in the resistance wire being firmly fixed in place during measurements under severe vibration, and makes it possible to eliminate fluctuations in the resistance value and breakage.

[0042] In this way, in the present invention, the insulating powder 4 is composed of a mixed glass powder containing a first glass powder and a second glass powder, and the inside of the insulator hole 20 has a connecting structure by the second glass powder, so that the resistance wire 3 is prevented from moving inside and being damaged. Furthermore, since the thermal expansion coefficient of the glass powder can be set to a value close to that of the resistance wire 3 as described above, a structure can be realized in which the resistance wire 3 is less susceptible to stress due to differences in thermal expansion, and it is possible to provide a product with excellent durability that can withstand impact and vibration.

[0043] When the average particle size of the first glass powder is larger than that of the second glass powder, the filling density of the insulating powder 4, which is the mixed glass powder, can be stably increased, thereby providing higher measurement accuracy and higher durability.

[0044] Furthermore, when the inter-wire distance in the central axis direction of the resistance wire coil inserted in the insulator is α (mm) and the average particle size of the first glass powder is β (mm), if the following formula (A1) is satisfied, the first glass powder can more reliably pass between the wires of the resistance wire to reach the outside (between the resistance wire and the inner wall of the insulator hole), the glass powder can more reliably fix the resistance wire coil in the insulator, the vibrations applied to the resistance wire in a high-vibration field can be more reliably absorbed, and durability can be reliably increased.

[0045]

number

[0046] Specifically, the insulating powder 4, which is a mixed glass powder, is filled by first connecting lead wires 5 to both ends of a spiral resistance wire 3, folding it back in a V-shape, inserting the lead wires 5 at both ends into the insulator hole 20, and protruding from the other end. The base end side from which the lead wires 5 protrude is sealed with a sealant 60, and then the insulating powder 4 is poured from the open hole on the opposite tip side. The insulating powder 4 flows from the top of the resistance wire 3 into the space inside the coil in the direction of the coil's central axis, and reaches the insulator hole wall from between the wires. After filling the insulating powder in this way, the tip side is sealed with a sealant 61 and heated to sinter the sealants 60 and 61 at both ends and soften or melt the second glass powder in the insulating powder 4 inside, and then cooling and solidifying the first glass powder, the first glass powder and the resistance wire, or the first glass powder and the inner surface of the insulator hole are connected via the second glass powder that has been softened or melted and solidified.

[0047] When filling the insulating powder 4, factors that hinder the filling of the fine insulating powder 4 into the fine insulator holes 20 include the problem of powder agglomeration due to humidity, van der Waals forces, static electricity, etc., so it is preferable to fill the powder while neutralizing static electricity using an electrostatic eliminator (ionizer) in a box from which moisture has been removed, in an environment that eliminates these problems.

[0048] Of the insulating powder 4 (mixed glass powder), at least the first glass powder is preferably spherical. This promotes the insulating powder 4, which is fed from one end of the insulator hole 20, to flow through the space inside the coil of the resistance wire inserted inside, and then the first glass powder passes between the wires of the resistance wire to reach the outside (between the resistance wire and the inner wall of the insulator hole), so that the resistance wire coil can be firmly fixed inside the insulator by the insulating powder 4. For example, the first glass powder can be spherical glass beads with a softening point temperature of 730°C and an average particle size of 15.6 μm, and the second glass powder can be glass frit with a softening point temperature of 394°C and an average particle size of 3.9 μm or less.

[0049] That is, as mentioned above, the insulating powder 4 is filled from the opening of the insulator hole, but in order for the insulating powder 4 to firmly fix the resistance wire 3, the powder added from above the resistance wire 3 must flow inside the coil shape of the resistance wire, pass between the coils, and reach the inner wall of the insulator hole. To achieve this, it is essential that the powder has a relatively large diameter so that it can move between the coils. For this reason, powder with a large particle size is preferably spherical, as it flows more easily. Also, by setting the maximum particle size at 20 μm, it becomes easier for the powder to pass between the coils and reach the inner wall of the insulator hole.

[0050] A schematic diagram of the state inside the insulator hole 20 filled with the insulating powder 4 is shown in Fig. 6. Also, Fig. 5 mentioned above is an SEM photograph of a cross section of a product actually produced by filling with 5 wt% of the second glass powder scattered among 95 wt% of the large-diameter first glass powder and melting or softening only the second glass powder.

[0051] Here, as shown in FIG. 7, if the large-diameter first glass is in a frit state, it may not reach the inner wall of the insulator hole through the gap between the resistance wires. Also, if the glass powder is too large, it will be unevenly distributed only in the coil. In contrast, if the average particle size of the first glass powder satisfies the above formula (A1), it can be seen that it reaches the inner wall of the insulator hole through the gap between the coils of the resistance wire as shown in the photograph of FIG. 5. It is preferable to set the particle size of the glass powder to 1 / 6 or less of the inner diameter of the coil of the resistance wire, for example, 30 μm or less, because this makes it easier to fill the coil without forming a powder bridge.

[0052] Furthermore, by using a particle size that allows two or three particles to be arranged between the coils of the resistance wire, the powder fills the inner wall of the insulator hole from the resistance wire, and the resistance wire can be firmly secured. For example, if the axial length of the insulator is 10 mm, the insulator hole is φ0.27 mm, and the resistance element is 100 Ω, the resistance wire diameter is 0.0125 mm (12.5 μm), and the coil length of the resistance wire is 6 mm, the resistance wire spacing is approximately 50 μm, and a particle size of about 20 μm is appropriate. Therefore, in order to avoid the formation of bridges when flowing in from above and to allow the powder to reach the inner wall of the insulator hole through the spaces between the resistance wires (coils), it is preferable to use a high-melting point glass as the first glass powder, in which 80% by weight or more of particles with a particle size distribution of 20 μm or less are present.

[0053] When a platinum resistance wire with a small diameter of approximately 0.01 mm is used as the resistance wire 3, if the temperature is raised to 500°C or higher when the second glass powder is softened or melted to deform and solidify, the resistance wire 3 will go beyond a recrystallized structure and the crystal grains will become coarse, and the coarse crystal grains will form a bamboo joint-like structure that crosses the wire diameter, making it more likely to break. The recrystallization of the resistance wire 3 begins at 400°C or higher, and the crystal grains become coarse at approximately 500°C in about an hour (of course, this depends on the degree of processing of the material and whether or not it has been heat-treated in advance).

[0054] Therefore, it is preferable that the first glass powder has a softening temperature of 500° C. or more, the second glass powder has a softening temperature of less than 500° C., and the second glass powder is softened or melted by heating at less than 500° C. to form a deformed and solidified connected structure. For example, the second glass powder is preferably a glass material that has a softening temperature of about 450° C. and can be heat-treated within 30 minutes. With regard to the particle size, it is preferable that the particle size is such that the glass material can be dispersed and attached to the surface of the larger first glass powder.

[0055] The resistance wire 3 and the lead wire 5 are connected by brazing. In conventional elements, connections were generally made by crimping or resistance welding, but repeated measurements at extremely low temperatures such as the temperature of liquid hydrogen and room temperature can cause changes in contact resistance due to thermal cycles and lead to disconnection due to poor connection. In this example, brazing is used to stabilize the resistance value in connecting a φ0.0125 mm (12.5 μm) resistance wire and a φ0.15 mm lead wire. In particular, in the low temperature range from room temperature to 20 K (-253°C), there is no resistance value fluctuation due to mutual reaction between the brazing material and the resistance wire, and a stable connection, i.e., a stable resistance value, is achieved.

[0056] Furthermore, when the resistance wire 3 is a thin platinum resistance wire, it is preferable to use a low-temperature brazing material with a liquidus temperature of less than 500° C. This can prevent deterioration of the platinum wire (the occurrence of bamboo-like knot structures) and breakage in a severe vibration field.

[0057] As shown in Fig. 8, the brazing connection is preferably performed by heating a position x1 of the lead wire 5 away from the pre-placed solder 8 while the connection end of the resistance wire 3 is in contact with or close to the pre-placed solder 8 provided on the connection end of the lead wire 5 on the resistance wire 3 side, and melting the pre-placed solder 8 by heat transfer caused by the heating, thereby connecting the resistance wire 3 to the lead wire 5. The lead wire 5 expands thermally when heated, so that it stretches slightly and the brazing of the resistance wire 3 and the solidification of the solder can be completed quickly. This process allows the melting of the solder material during connection to be completed in a short time, suppresses unnecessary heat input to the resistance wire, and prevents the occurrence of the bamboo knot-like structure mentioned above.

[0058] Furthermore, it is preferable that the lead wire 5 is heated by a pulsed laser welder 7 using a predetermined number of pulse heating processes. Since the solder portion is not directly heated by irradiating it with a laser, unnecessary heating of the resistance wire can be avoided by shifting the focus of the laser from the resistance wire.

[0059] It is preferable to heat the wax by the number of pulses necessary to melt the predetermined amount of wax, for example, 5 pulses per set. This method can reduce excess heat input to the wax as much as possible, more reliably prevent the bamboo knot structure from occurring, and stabilize the quality and improve the efficiency of production.

[0060] As the brazing material, it is preferable to use, for example, a low-temperature brazing material such as an alloy of 82% gold and 18% indium called gold-indium solder, which has a solidus temperature of 450° C. and a liquidus temperature of 485° C., or a low-temperature brazing material such as gold-germanium solder, which has a solidus temperature of 360 to 480° C. In particular, when gold-germanium solder is used, the softening temperatures of the second glass powder and the sealing material at both ends of the insulator hole may be adjusted so as to be lower than the solidus temperature of the brazing material depending on the type of brazing material used.

[0061] Although the embodiment of the present invention has been described above, the present invention is not limited to these embodiments, and it is of course possible to carry out the present invention in various forms without departing from the gist of the present invention. EXAMPLES

[0062] Next, the results of a thermal cycle test in which a sample according to the present invention (Example 1) and a conventional sample (Comparative Example 1) were used to measure the amount of change in temperature deviation before and after thermal cycle treatment will be described.

[0063] (Sample of Example 1) A hundred identical resistance temperature detector elements having the structure according to the present invention shown in Fig. 4 were prepared. Each part is as follows. Lead wire: platinum-rhodium alloy resistance measurement lead with an outer diameter of 0.15 mm Ceramic insulator: A heat-resistant insulator (alumina two-hole insulator) with an outer diameter of φ0.8 mm, a length of 10 mm, and two insulator holes with a hole diameter of φ0.27 mm that penetrate in the axial direction. Resistance wire: Platinum resistance wire (Pt99.999+wt%), wire diameter φ0.0125mm (12.5μm) spiral (coil) resistance wire, coil center diameter PCD 0.2mm+α, coil outer diameter φ0.225mm+α, coil length 6mm, coil spacing approximately 50μm Insulation powder: Mixture of first and second glass powders First glass powder: softening point of 730°C, average particle size (particle size at 50% cumulative value in particle size distribution obtained by Coulter counter method) of 15.6 μm, thermal expansion coefficient of 88×10 -7 / ℃ (same as platinum resistance wire) glass beads Second glass powder: softening point of 394°C, average particle size (particle size at 50% cumulative value in particle size distribution obtained by laser diffraction / scattering method) of 3.9 μm, thermal expansion coefficient of 105×10 -7 / ℃ Glass Frit Glass powder mixing ratio (mass ratio): 1st glass powder / 2nd glass powder=95 / 5 Mix evenly with a mixer. Extension lead wire: Platinum-rhodium alloy (Pt-Rh 10% by weight), wire diameter φ0.15, lead wire length 15mm - Soldering material for connecting lead wire and resistance wire: Gold solder (K10 solder (contains 41.7% gold by weight, working (melting) temperature 740℃)) Sealing material on both ends of the insulator hole: Low-temperature firing seal paste mainly composed of SiO2·B2O3 / PbO (AGC Corporation seal glass "AP4290D1", softening point 405℃, average particle size 3.5μm, thermal expansion coefficient 78(×10 -7 / ℃)

[0064] To manufacture the insulator, first insert a resistance wire, with lead wires already connected to both ends with solder, into the insulator hole of the ceramic insulator, and seal one end of the insulator, for example the base end, which is the lead side, with a sealant. The sealed end is then set upright with the insulator facing down, and insulating powder is poured into the inside of the resistance wire inserted in the insulator hole from the other end facing up, for example the tip side. The insulating powder is filled by applying vibration to the ceramic insulator to prevent clogging along the way, causing it to fall toward the base end. Then, a heat treatment is applied to sinter and solidify the sealants at both ends, and the low-melting point glass inside partially fixes the high-melting point glass (Figure 5).

[0065] (Sample of Comparative Example 1) As a conventional sample (Comparative Example 1), 100 resistance temperature detector elements "P100 / 1008" (outer diameter φ0.8 mm, length 10 mm) manufactured by TDI were prepared.

[0066] (Thermal cycle treatment method and results) The thermal cycle treatment involved placing each sample in a polyimide tube and repeatedly subjecting the sample to a thermal cycle of room temperature ⇔ liquid nitrogen temperature (-196°C) several times while preventing liquid nitrogen from coming into direct contact with the element. The specific number of thermal cycles was 10 times for the sample of Example 1 and 10 times for the sample of Comparative Example 1. The change in resistance value at 0°C before and after the thermal cycle treatment was then measured. The results are shown in the graph of FIG. 9 and Table 1.

[0067] As can be seen from Fig. 9 and Table 1, the sample of Example 1 has a smaller temperature deviation change due to the thermal cycle and the variation is also kept small compared to the sample of Comparative Example 1. The reason why the sample of Example 1 showed better results than Comparative Example 1 is thought to be because the high-melting point glass, which accounts for 95% of the insulating powder, has a thermal expansion coefficient close to that of the resistance wire, thereby minimizing the generation of thermal stress due to the thermal cycle. It can also be seen that the product of the present invention is not affected by the difference in the thermal expansion coefficient between the platinum resistance wire, the low-melting point glass, and the insulating insulator.

[0068] [Table 1]

[0069] Next, the same test as the above thermal cycle test was continued for each sample of Example 1 and Comparative Example 1 until 100 passing products were obtained (i.e., the remaining 5 samples of Example 1 and the remaining 29 samples of Comparative Example 1 were continued until all passing products were obtained), and each of these passing samples (100 samples of Example 1, 100 samples of Comparative Example 1, a total of 200 samples) was subjected to further vibration using a vibration tester, and the presence or absence of disturbance in the internal resistance wire coil before and after vibration was determined by X-ray photography, and the amount of change in temperature deviation before and after vibration was measured. The vibration test results will now be described.

[0070] (Test Method) Vibration tester: IMV Corporation "i220 / SA1M" Vibration conditions: The sample of Comparative Example 1 was subjected to an AT test (Acceptance Test) at a vibration level of 23.4 Grms for 1 minute, and the sample of Example 1 was subjected to a QT test (Qualification Test) at a vibration level of 46.8 Grms for 2 minutes (vibration level and vibration time were twice those of the AT test). Evaluation method: X-rays were taken of each sample before and after vibration, and the position of the internal resistance wire coil was compared to determine whether any disturbance (change in coil position) had occurred.

[0071] (Test Results) As can be seen from Table 2, in terms of coil disorder, 98 out of 100 samples (98%) of Example 1 (100 samples that passed the thermal cycle test) passed, with almost no disorder. In contrast, 54 out of 100 samples (54%) of Comparative Example 1 (100 samples that passed the thermal cycle test) passed, with the remaining 46 samples, or roughly half, showing coil disorder. It can be seen that the product of the present invention has excellent durability against shock and vibration. Note that FIG. 10 shows examples of X-ray photographs of a sample of Example 1 that passed (no disorder) and a sample of Comparative Example 1 that did not pass (disordered). Moreover, as shown in Table 2 and FIG. 11, the amount of change in temperature deviation before and after the vibration test was almost the same, with 95 or more samples passing in both Example 1 and Comparative Example 1.

[0072] [Table 2]

[0073] Next, for samples of connections in which the resistance wire and lead wire are connected before being incorporated into the insulator, two types (Examples 2 and 3) were prepared using different methods of connecting the resistance wire and the lead wire. For each connection sample, the outer surface structure of the connection part was observed and a tensile strength test of the resistance wire was performed. The results are shown below.

[0074] (Sample of connector) Lead wire: platinum-rhodium alloy resistance measurement lead with an outer diameter of 0.15 mm Resistance wire: Platinum resistance wire (Pt99.999+wt%), wire diameter φ0.0125mm (12.5μm) spiral (coil) resistance wire, coil center diameter PCD 0.2mm+α, coil outer diameter φ0.225mm+α, coil length 6mm, coil spacing approximately 50μm In connections using the same gold brazing material, the samples of Example 2 were connected by processing using pulse heating (160 V) a predetermined number of times (1 to 3 sets, with 5 pulses being one set) using a pulse laser welder 7 shown in Figure 8, and the samples of Example 3 were connected by processing using frame brazing with an oxygen-acetylene flame.

[0075] (Observation results of the outer surface structure of the joint) Figures 12 and 13 show SEM photographs of the structure of the outer surface of the connection part of each connection sample of Examples 2 and 3. In Example 3, as can be seen from Figure 12, a bamboo structure appears on the outer surface in the crystalline structure near the brazed part. However, in Example 2, which was brazed with a pulsed laser, as can be seen from Figure 13, it remains a polycrystalline structure even though a brazing material with the same liquidus temperature was used.

[0076] (Tensile test results) The tensile strength of the resistance wire in Example 3 is 1N / mm 2 The tensile strength of the resistance wire of Example 2 brazed with pulsed laser is 4N / mm 2 This shows that the intensity is about four times higher. When the state of the broken wire at the fractured portion was observed with a stereo microscope, the bamboo structure showed brittle fracture, as shown in the photograph in Figure 14. Furthermore, from the above results, it can be seen that the soundness of the brazing can be confirmed by using a stereo microscope or SEM to confirm the homogeneity of the brazing and the absence of bamboo formation on the resistance wire surface structure. [Explanation of symbols]

[0077] 1 Resistance temperature sensor element 2 Insulators 3. Resistance Line 4. Insulation Powder 5 Lead Wire 20 Insulator hole 40 First glass powder 41 Second Glass Powder 60 Encapsulating material 61 Encapsulating materials

Claims

1. A connection method for connecting a resistance wire of a resistance temperature sensor element, the resistance wire being fixed inside the insulator hole of a ceramic insulator by inserting a coil of a spiral resistance wire into the insulator hole and filling a gap between the insulator hole and the resistance wire with insulating powder, coaxially connecting the resistance wire to a lead wire with their end faces butted against each other, comprising: Place the lead wire on the connection end surface of the resistance wire side and solder it. The solder joint and the connection end surface of the resistance wire are brought into contact with each other or into close proximity with each other, In the contact or proximity state, a position of the lead wire separated from the solder is heated; The solder is melted by heat transfer due to the heating and connected to the connection end surface of the resistance wire. How to connect the resistance wire and lead wire of a resistance temperature sensor element.

2. 2. The method for connecting a resistance wire and a lead wire according to claim 1, wherein the lead wire is heated by a pulse laser welder through a predetermined number of pulse heating processes.

3. 2. The method for connecting a resistance wire and a lead wire according to claim 1, wherein a low-temperature brazing material is used as the brazing material for the pre-placed brazing material.

Citation Information

Patent Citations

  • Locking device

    JP1977016947A

  • Reflow soldering method

    JP1985261665A

  • Temperature measuring resistor

    JP1987070721A

  • Temperature sensor and temperature measuring element

    JP1992005527A

  • Laser brazing method

    JP1997216051A